Strengthening Individual Taxpayer Compliance: The Impact of Tax Sanctions and Regulatory Review - Sri Depi; Siswati Rachman; Nur Fadny Yuliani; Imran Tahalua; Nur Sandi Marsuni (Universitas Muhammadiyah Makassar, 2024)
This research aims to provide empirical evidence regarding the influence of tax sanctions on individual taxpayer compliance. This type of research is carried out using literature observation, namely research that studies written documentary materials such as books, articles, journals, news and other types of literature related to a theme as the main object. This research examines various literature to find out how tax sanctions can influence taxpayer behavior. The research results show that tax sanctions have a positive and significant effect on individual taxpayer compliance. The higher the taxpayer's tax awareness, the higher the level of taxpayer satisfaction. With strict sanctions, taxpayers become more aware of their obligations and more motivated to comply with tax regulations. This research reveals that effective tax sanctions policies can increase the level of taxpayer compliance and reduce the problem of non-compliance caused by factors such as public dissatisfaction with public services, uneven infrastructure development, and high levels of corruption among high-ranking officials. Public dissatisfaction with government services often makes taxpayers feel that their tax payments are not used efficiently, while inequality in infrastructure development can create feelings of injustice among taxpayers, ultimately reducing their motivation to comply with tax obligations. High levels of corruption among high-ranking officials also exacerbate this situation by reducing public trust in the government. By reviewing various literature, this research highlights the importance of tax sanctions as a tool to increase tax compliance. This shows that a firm and consistent policy in implementing tax sanctions can help improve the level of tax compliance and overcome challenges caused by dissatisfaction with public services and other problems.